1993
DOI: 10.1109/23.273476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of process parameter distributions and ion strike locations on SEU cross-section data (CMOS SRAMs)

Abstract: The effect of statistical parameter distributions and stochastic ion strike locations in hardened memory arrays on observed SEU cross-section data is discussed. Application of numerical analysis to the parasitic bipolar gain distributions in SIMOX SRAMs and the introduction of an effective critical charge based on sensitivities to ion strike locations, explains and quantifies the non-saturating behavior of measured cross-section curves in SO1 and other hardened memories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…This was noted by Petersen [6] and later by Barak et al [7] when discussing the cross section associated with the charge-collection depth exceeding a specified value. Petersen has also used other terminology, a charge-collection gain [8], following Massengill et alwho reported that some devices exhibit a parasitic bipolar gain that varies as ion hit location is varied [9]. The first physical postulate stated in the previous subsection implies that the charge-collection depth at a given lateral location is the integral of along a perpendicular line through the device at that lateral location.…”
Section: B the Second Postulatementioning
confidence: 99%
See 4 more Smart Citations
“…This was noted by Petersen [6] and later by Barak et al [7] when discussing the cross section associated with the charge-collection depth exceeding a specified value. Petersen has also used other terminology, a charge-collection gain [8], following Massengill et alwho reported that some devices exhibit a parasitic bipolar gain that varies as ion hit location is varied [9]. The first physical postulate stated in the previous subsection implies that the charge-collection depth at a given lateral location is the integral of along a perpendicular line through the device at that lateral location.…”
Section: B the Second Postulatementioning
confidence: 99%
“…The solid angle integral of the above equation produces a heavy-ion SEU rate in an isotropic environment (with the integral LET flux proportional to ) on the right side. The result is day-cm cm coul-m (9) where is defined by Heavy-ion rate for a device having a normal-incident cross section and produced by an integral LET flux given by m -sec-ster MeV-cm mg . The constant in the flux was selected so that inconvenient constants do not appear in (9).…”
Section: B Evaluation Via a Heavy-ion Rate Calculationmentioning
confidence: 99%
See 3 more Smart Citations